PERLINDUNGAN HUKUM TERHADAP LAHAN PRODUKTIF PERTANIAN AKIBAT MARAKNYAALIH FUNGSI LAHAN UNTUK KEPERLUAN PROPERTI, INDUSTRI DAN PROYEK PEMBANGUNAN STRATEGIS NASIONAL BERDASARKAN HUKUM POSITIF INDONESIA - Hotris Parlinggoman Sitanggang; Mella Ismelina F. Rahayu (Fakultas Hukum Universitas Tarumanagara, 2022)
The rise of conversion of productive agricultural land to non-agricultural purposes for properti, industry andnational strategic development projects has threatened the existence of agricultural land which in the endcan also threaten national food security, so the problem arises how to regulate agricultural land that can beallowed to be converted to non-agricultural based on positive law in Indonesia and what are the forms oflegal protection for agricultural productive land against the widespread conversion of land for properti,industry and national strategic development projects based on Indonesian positive law. The research methodused is normative juridical which is descriptive analytical. Based on the results of the analysis thatagricultural land that has been determined can be converted for public interest and national strategicdevelopment by fulfilling certain conditions based on Article 44 Paragraph (2) of the PLP2B Law, and forindustrial purposes the criteria for land that can be converted are dry land and less fertile. The form of legalprotection is that the government has issued several legal regulations, but in its implementation in theregions it has not yet established protected areas of sustainable agricultural land so that the protection ofproductive agricultural land has not been implemented properly. Another form of protection provided isincentives for land-owning farmers whose lands are willing to be determined on the Protected Paddy FieldMap (PLSD).